The Functioning of the Brain Trained by Neurofeedback with Behavioral Techniques from a Learning Curve Perspective - Ribas, Valdenilson Ribeiro; Ribas, Renata de Melo Guerra; de Oliveira, Diélita Carla Lopes; Regis, Carmen Luciane Souza; Filho, Paulo Cezar do Nascimento; Sales, Tales de Souza Roberto; Martins, Hugo André de Lima; Deusen, Peter Van (Journal of Psychology and Psychotherapy Research, 2016)
The learned reflex behavior (Reaction) of Ivan Pavlov (1849-1936) and operant behavior (Action) of Burrhus Skinner (1904-1990) have been used as technical approaches from the perspective of the learning curve through repetitious training using neurofeedback. The aim of this study was to describe the meaning and application of these associated approaches and to explain their neurophysiological implications. A review of the MEDLINE/PubMed and Web of Science electronic databases was carried out from March to October 2016. The learning curve is a graphical representation of the increase in learning from experience (repetitions). Thus, for example, an anxious state caused by behavior such as thinking about the future and the past, complaining, criticizing, judging and analyzing in excess, can be modified by training concentration (operant/action behavior), thereby reducing the excess of fast waves in the hindbrain (learned/reaction reflex behavior), leading the subject from the dysphoric state to a state of well-being.